Resveratrol Enhances Etoposide‐Induced Cytotoxicity through Down‐Regulating ERK1/2 and AKT‐Mediated X‐ray Repair Cross‐Complement Group 1 (XRCC1) Protein Expression in Human Non‐Small‐Cell Lung Cancer Cells. Issue 6 (30th June 2015) - Ko, Jen‐Chung; Syu, Jhan‐Jhang; Chen, Jyh‐Cheng; Wang, Tai‐Jing; Chang, Po‐Yuan; Chen, Chien‐Yu; Jian, Yun‐Ting; Jian, Yi‐Jun; Lin, Yun‐Wei
Abstract: Etoposide (VP‐16), a topoisomerase II inhibitor, is an effective anti‐cancer drug used for the treatment of non‐small‐cell lung cancer (NSCLC). Resveratrol is a naturally occurring polyphenolic compound that has been proved to have anti‐cancer activity. XRCC1 is an important scaffold protein involved in base excision repair that is regulated by ERK1/2 and AKT signals and plays an important role in the development of lung cancer. However, the role of ERK1/2 and AKT‐mediated XRCC1 expression in etoposide treatment alone or combined with resveratrol‐induced cytotoxicity in NSCLC cells has not been identified. In this study, etoposide treatment increased XRCC1 mRNA and protein expression through AKT and ERK1/2 activation in two NSCLC cells, H1703 and H1975. Knockdown of XRCC1 in NSCLC cells by transfection of XRCC1 siRNA or inactivation of ERK1/2 and AKT resulted in enhancing cytotoxicity and cell growth inhibition induced by etoposide. Resveratrol inhibited the expression of XRCC1 and enhanced the etoposide‐induced cell death and anti‐proliferation effect in NSCLC cells. Furthermore, transfection with constitutive active MKK1 or AKT vectors could rescue the XRCC1 protein level and also the cell survival suppressed by co‐treatment with etoposide and resveratrol. These findings suggested that down‐regulation of XRCC1 expression by resveratrol can enhance the chemosensitivity of etoposide in NSCLC cells.